The Genomic Blueprint of Salmonella enterica subspecies enterica serovar Typhi P-stx-12. Issue 3 (November 2013) - Ong, Su; Bhan Pratap, Chandra; Wan, Xuehua; Hou, Shaobin; Rahman, Ahmad; Saito, Jennifer; Nath, Gopal; Alam, Maqsudul
Abstract Salmonella enterica subspecies enterica serovar Typhi is a rod-shaped, Gram-negative, facultatively anaerobic bacterium. It belongs to the familyEnterobacteriaceae in the classGammaproteobacteria, and has the capability of residing in the human gallbladder by forming a biofilm and hence causing the person to become a typhoid carrier. Here we present the complete genome ofSalmonella enterica subspecies enterica serotype Typhi strain P-stx-12, which was isolated from a chronic carrier in Varanasi, India. The complete genome comprises a 4, 768, 352 bp chromosome with a total of 98 RNA genes, 4, 691 protein-coding genes and a 181, 431 bp plasmid. Genome analysis revealed that the organism is closely related toSalmonella enterica serovar Typhi strain Ty2 andSalmonella enterica serovar Typhi strain CT18, although their genome structure is slightly different.